The potential of biodiesel production from grasses in Thailand through consolidated bioprocessing using a cellulolytic oleaginous yeast, Cyberlindnera rhodanensis CU-CV7. (15th January 2023) - Chuengcharoenphanich, Nuttha; Watsuntorn, Wannapawn; Qi, Wei; Wang, Zhongming; Hu, Yunzi; Chulalaksananukul, Warawut
Abstract: Biodiesel can be produced from lipids derived from the cellulolytic oleaginous yeast Cyberlindnera rhodanensis CU-CV7 when directly cultivated on undetoxified Thai-grass hydrolysates through consolidated bioprocessing (CBP). The lipid content of CU-CV7 grown on a glucose-based medium was 26.77 ± 0.56% of the cell dry weight (CDW). Strain CU-CV7 is a great CBP-enabling microbe because of its native capacity to generate lipid (22.19 ± 0.72% of CDW) while simultaneously expressing endoglucanase, exoglucanase, and β-glucosidase activities (0.33, 0.06, and 0.20 IU/mL, respectively) on carboxymethylcellulose. Strain CU-CV7 was demonstrated to be a lipase-producing strain and could potentially be employed as a biocatalyst to produce biodiesel with a maximum extracellular lipase activity of 1.47 IU/mL. The lipid production from 13 types of grass without the need for additional cellulase was evaluated. The highest lipid yield was obtained from Napier (Lampang ecotype; 1.01 ± 0.14 g/L) and was comprised of a high proportion of saturated fatty acids. The predicted biodiesel properties were found to be suitable with respect to the biodiesel international standards. Thus, lipid production from these grasses by CU-CV7 appears to open a new path for the renewable biodiesel industry and to satisfy the SDG 7 and SDG 13 goals. Graphical abstract: Image 1 Highlights: Cyberlindnera rhodanensis CU-CV7 was defined as a cellulolytic oleaginous yeast. CU-CV7 accumulated lipid and presented cellulase activities in CMC medium. CU-CV7 directly grew and produced lipids for biodiesel on Thai grass via CBP. CU-CV7 recognized as a lipase-producing yeast when using palm oil as a lipid source. The fatty acid composition demonstrated a potential high biodiesel quality.